2008
DOI: 10.1038/bmt.2008.326
|View full text |Cite
|
Sign up to set email alerts
|

Immunogenic disparities of 11 minor histocompatibility antigens (mHAs) in HLA-matched unrelated allogeneic hematopoietic SCT

Abstract: We determined the alleles of 11 mHAs and investigated the association of immunogenic mHA mismatches between a donor and a recipient with a course of allogeneic hematopoietic SCT (allo-HSCT) from 10/10 alleles HLA-matched unrelated donors in 92 recipients after myeloablative conditioning between 2004 and 2006. The frequency analysis of mHA alleles, genotypes and phenotypes accompanied by appropriate restriction HLA Ags allowed for an estimation of the probability of immunogenic mismatches, which was the highest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
12
1

Year Published

2012
2012
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 43 publications
(35 reference statements)
4
12
1
Order By: Relevance
“…These results correspond to the reported influence of sex difference on transplant outcomes, especially in the case of female donor to male recipient (FDMR) transplants [61, 62]. Oppositely, Markiewicz et al in a study of 92 unrelated donor-recipient pairs found that HY mismatches in GVH direction influenced more favorable GVL effect than unfavorable GVHD, what resulted in the increased DFS ( P = 0.05) [12, 63]. The probable explanation of this difference in MiHAs impact on OS and DFS between related and unrelated allo-HCT may be the use of stronger standard immunosuppressive prophylaxis including pretransplant antithymocyte globulin in unrelated allo-HCT setting.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…These results correspond to the reported influence of sex difference on transplant outcomes, especially in the case of female donor to male recipient (FDMR) transplants [61, 62]. Oppositely, Markiewicz et al in a study of 92 unrelated donor-recipient pairs found that HY mismatches in GVH direction influenced more favorable GVL effect than unfavorable GVHD, what resulted in the increased DFS ( P = 0.05) [12, 63]. The probable explanation of this difference in MiHAs impact on OS and DFS between related and unrelated allo-HCT may be the use of stronger standard immunosuppressive prophylaxis including pretransplant antithymocyte globulin in unrelated allo-HCT setting.…”
Section: Discussionsupporting
confidence: 82%
“…Japanese group found that GVH-directed HA-1 mismatches were associated with lower risk of relapse [51]. Similarly, experience of Polish group studying MiHAs in unrelated allo-HCT showed seldom episodes of relapse occurring when GVH-directed HY mismatches were present [63]. …”
Section: Discussionmentioning
confidence: 99%
“…Numerous MiHAs have been identified in the past decades and T cell responses against these MiHAs have been associated with improved relapse-free survival. While in some studies the induction of MiHA-specific T cell responses was associated with an increase in the incidence of GVHD and improved relapse-free survival, [18][19][20][21] other studies could not confirm these results. 22,23 Importantly, boosting of T cell responses against MiHAs with a hematopoietic-restricted expression pattern, e.g., HA1, 24 LRH1, 25 ARHGDIB, 26 and UTA2-1 27 has the potential to induce a selective GVM effect with only limited risk of eliciting GVHD.…”
Section: Lessons From Allogeneic Sctcontrasting
confidence: 41%
“…Furthermore, previous studies have predominantly investigated cohorts of HLA-matched non-T cell-depleted transplants, and found only an increase in chronic GVHD (cGVHD) and reduced relapse rate upon HY MiHA disparity. 17;18 Moreover, investigation of the role of MiHA incompatibility in transplant outcome is hampered by the requirements to restrict studies to specific HLA types and low frequencies of particular MiHA alleles. Recently however, it was reported that HLA-A2 + chronic myeloid leukemia (CML) patients who developed acute GVHD (aGVHD) showed an improved overall survival (OS) and relapse-free survival (RFS) when receiving a transplant from a HA1-mismatched donor.…”
Section: Introductionmentioning
confidence: 99%